Labor market frictions and monetary policy design - Anna Almosova (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2016)
This paper estimates a New Keynesian DSGE model with search frictions and monetary rules augmented with different labor market indicators. In accordance with a theoretical literature I find that a central bank reacts to a labor market tightness, employment or unemployment. Posterior odds tests speak in favor of models with augmented Taylor rules versus a model with a model with a standard rule. The augmented rules were also shown to be more efficient in terms of welfare.
Keywords: E52; E24; C11; 330; Search frictions; Optimal monetary policy; Bayesian estimation; Taylor rules